Effect of the nitrogen concentration on the morphological attributes, root growth potential and nutritional status on cover root Eucalyptus globulus seedlings - Acevedo, Manuel; Monsalve, Jordán; Escobar, René; Sánchez, Manuel; Coopman, Rafael (BOSQUE, 2009)
Four nitrogen concentrations (50, 100, 150, and 200 mg L–1) were evaluated on shoot and root growth, root growth potential, and nutritional status of cover root Eucalyptus globulus seedlings. Nutrient solutions were applied on a weekly basis together with irrigation. All other elements were held constant in the nutrient solutions. Irrigation was applied considering a 20% loss of the seedling tray. Plant height and leaf area reached their peak at 200 mg L–1; collar diameter, number and the absolute weight of new roots did not change when concentrations where 150 or 200 mg L–1. For all treatments the best results were obtained when the fertilization was made with 200 mg L–1 because it produced plants with higher root growth potential and better morphological attributes, with the only disadvantage of low levels of foliar nitrogen obtained at the end of the essay.